28‐1: Image Capture Through TFT Arrays. Issue 1 (25th September 2020) - Emerton, Neil; Ren, David; Large, Tim
Abstract : Images captured through displays are dim and blurred owing to attenuation and diffraction. Display structures can result in angular frequencies in the scene being completely blocked. We describe an optical method to recover these frequencies resulting in a more complete capture of the scene.